Contibution of Sharia fintech to micro, small, and medium enterprises’ inclusivity in Kisaran City - Maharani, Sri; Nurbaiti, Nurbaiti; Dharma, Budi (Journal of Islamic Economics Lariba, 2024)
IntroductionChallenges in access to inclusive financial services are still a major issue for many micro, small and medium enterprises in Indonesia, including in Kisaran City. However, research that specifically discusses this is still rarely carried out.ObjectivesThis research aims to analyze the role of sharia fintech in increasing the inclusiveness of micro, small and medium enterprises in Kisaran City.MethodThis research uses qualitative approach with primary data is obtained by interviewing three MSMEs owners using Sharia fintech. Secondary data is collected from books, the internet, academic journals, archives, and official records.ResultsThe results of this research show an increase in the use of Sharia Fintech by micro, small and medium enterprises in Kisaran City in 2020-2023. Apart from that, the use of Sharia fintech has a positive influence in increasing financial inclusiveness and encouraging the growth of micro, small and medium enterprises in Kisaran City..ImplicationsMicro, small and medium enterprises can use financial services from sharia fintech to increase access to funding and to expand customer payment models. Policy makers can continue to increase the role of sharia fintech for inclusiveness of micro, small and medium enterprises through more certain regulations and also increasing public education.Originality/NoveltyThis study contributes to enrich studies in the field of financial inclusion for micro, small, and medium enterprises with emphasize on the use of fintech.